2011
DOI: 10.3141/2243-16
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Human, Machine, and Environment in Automated Driving Systems

Abstract: In view of the increase in traffic volume and growing demands on traffic, alternative mobility concepts such as automation of the driving task are increasingly being investigated. In line with this course of development project KONVOI was initiated, where an interdisciplinary research team carried out the electronic coupling of trucks. Because the technical feasibility of such automated systems had already been proved, project KONVOI focused on quantifying the impact of automated systems on traffic and on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Another simulator study by Young (2000) found no differences between ACC and HAD regarding the number of drivers who responded to the automation failure occurring without salient warning at the same time as the lead car started braking (27 of 44 participants responded to the ACC failure, and 25 of 44 participants responded to the HAD failure). In Lank, Haberstroh, and Wille (2011), truck drivers experienced a HAD system in a simulator. No statistically significant difference was found between manual and HAD regarding the drivers' reaction time to an unexpected deceleration of the leading vehicle without brake lights.…”
Section: Had Versus Manual/acc Drivingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another simulator study by Young (2000) found no differences between ACC and HAD regarding the number of drivers who responded to the automation failure occurring without salient warning at the same time as the lead car started braking (27 of 44 participants responded to the ACC failure, and 25 of 44 participants responded to the HAD failure). In Lank, Haberstroh, and Wille (2011), truck drivers experienced a HAD system in a simulator. No statistically significant difference was found between manual and HAD regarding the drivers' reaction time to an unexpected deceleration of the leading vehicle without brake lights.…”
Section: Had Versus Manual/acc Drivingmentioning
confidence: 99%
“…The second school of thought argues that a human operator is vital in a highly automated system (Merat & Lee, 2012;Nilsson, 2005) and that driver of a highly automated car should not have a passive role (De Waard et al, 1999). Developers of an automated driving system that could drive for hours on a highway argued that concentration is constantly required despite the monotonous situation (Lank et al, 2011). A parallel of the second school of thought may be found in aviation.…”
Section: Remaining Human Factors Questionsmentioning
confidence: 99%
“…Insofar, the studies on the CACC impact on HVs are relatively scarce in the literature. The majority of the CACC study for human factors pertains to the human-machine interface, especially for the transition of authority at a low or medium level of automation (Berghöfer et al, 2018;Lank et al, 2011;Naujoks et al, 2017;Shen and Neyens, 2017). Nowakowski et al (2010Nowakowski et al ( , 2011 studied the acceptance of the short following time headway (ranging from 0.6 s to 1.1 s) enabled by CACC.…”
Section: Relevant Researchmentioning
confidence: 99%
“…Although different future platoon implementations can be envisaged (e.g. Martens et al, 2007), current concepts assume a system whereby the platoon is led by a trained, professional driver whilst the following vehicles are driven fully automatically by the system (Robinson et al, 2010;Lank et al, 2011). Compared to with ACC, platoon driving is extending the automation of the driving task considerably by adding lateral vehicle control which, in essence, leaves the driver free to relax or engage in non-driving tasks.…”
Section: Platoon Drivingmentioning
confidence: 99%
“…Platoon driving is predicted to provide a range of advantages (see Robinson et al, 2010;Lank et al, 2011). First, the small headways maintained in platoons results not only in a reduction in drag and associated energy efficiency, but also an increase in road network capacity due to the mere fact that less road space is required.…”
Section: Platoon Drivingmentioning
confidence: 99%